Differential Expression of Immune Checkpoint Modulators on In Vitro Primed CD4+ and CD8+ T Cells - Sabins, Nina C.; Harman, Benjamin C.; Barone, Linda R.; Shen, Shixue; Santulli-Marotto, Sandra (Frontiers in Immunology, 2016)
PD-1, TIM-3 and LAG-3 are molecules shown to have immune modulatory properties and although initially classified as indicators of T cell hyporesponsiveness, it has become clear that they are also associated with the normal course of T cell activation. Functional studies have focused mainly on CD8+ T cells during chronic inflammation due to interest in co-opting the cellular immune response to eliminate viral or cancerous threats; however, there remains a relative lack of data regarding expression of these molecules on CD4+ T cells. Here, we report that expression of the immune checkpoint (IC) molecules PD-1, LAG-3, and TIM-3 are differentially expressed on CD4+ and CD8+ T cells in the allogeneic response resulting from a mixed lymphocyte reaction. In these studies, PD-1 expression is higher on CD4+ T cells compared to CD8+ T cells. In contrast, TIM-3 is expressed at higher levels on CD8+ T cells compared to CD4+ T cells with an apparent reciprocity in that PD-1+ CD4+ T cells are frequently TIM-3lo/- while TIM-3 expressing CD8+ T cells are largely PD-1lo/-. In addition, there is a decrease in the frequency of TIM-3+ CD4+ cells producing IFN- and IL-5 compared to TIM-3+CD8+ cells. Lastly, the memory T cell phenotype within each IC-expressing subset differs between CD4+ and CD8+ T cells. These findings highlight key differences in immune checkpoint expression patterns between CD4+ and CD8+ T cells and may allow for more effective therapeutic targeting of these molecules in the future.